A Collaborative Of Leading Health Systems Finds Wide Variations In Total Knee Replacement Delivery And Takes Steps To Improve Value - Tomek, Ivan M.; Sabel, Allison L.; Froimson, Mark I.; Muschler, George; Jevsevar, David S.; Koenig, Karl M.; Lewallen, David G.; Naessens, James M.; Savitz, Lucy A.; Westrich, James L.; Weeks, Bill; Weinstein, James (Health Affairs, 2012)
Members of a consortium of leading US health care systems, known as the High Value Healthcare Collaborative, used administrative data to examine differences in their delivery of primary total knee replacement. The goal was to identify opportunities to improve health care value by increasing the quality and reducing the cost of that procedure. The study showed substantial variations across the participating health care organizations in surgery times, hospital lengths-of-stay, discharge dispositions, and in-hospital complication rates. The study also revealed that higher surgeon caseloads were associated with shorter lengths-of-stay and operating time, as well as fewer in-hospital complications. These findings led the consortium to test more coordinated management for medically complex patients, more use of dedicated teams, and a process to improve the management of patients' expectations. These innovations are now being tried by the consortium's members to evaluate whether they increase health care value.